Childhood Glaucoma - Weinreb, R. N; Grajewski, A. J; Papoudopoulos, M (Kugler Publications, 2013)
PrefaceChild hood is the topic of the ninth World Glaucoma Association Consensus. There has been only sparse attention to the diagnosis and treatment of childhood glaucoma. Both pediatric ophthalmologists and glaucoma specialists provide care for such children. In some instances, they manage these individuals alone and, in others, the management is shared. For this consensus, the participation of both groups was solicited. The global faculty, consisting of leading authorities on the clinical and scientific aspects of childhood glaucoma, met in Vancouver on July 16, 2013, just prior to the World Glaucoma Congress, to discuss the reports and refine the consensus statements.As with prior meetings, it was a daunting task to seek and obtain consensus on such a complicated and nuanced subject. It is unclear how each of us decides how we practice, and evidence to guide us often is sparse. It is remarkable how few high level studies have been conducted on the management of childhood glaucoma. Hence, this consensus, as with the others, is based not only on the published literature, but also on expert opinion. Although consensus does not replace and is not a surrogate for scientific investigation, it does provide considerable value, especially when the desired evidence is lacking.The goal of this consensus was to provide a foundation for diagnosing and treating childhood glaucoma and how it can be best done in clinical practice. Identification of those areas for which we have little evidence and, therefore, the need for additional research also was a high priority. We hope that this consensus report will serve as a benchmark of our understanding. However, this consensus report, as with each of the others, is intended to be just a beginning. It is expected that it will be revised and improved with the emergence of new evidence.Robert N. Weinreb, Chair.